اسلامی مالیات : معاصر اداروں کا تعارفی مطالعہIslamic Finance: An Introductory Study of Contemporary Institutions (Al-Qamar, 2021)
This paper aims at presenting an introductory study of contemporary Islamic financial institutions. It finds that after political weakness of the Islamic world and domination of Western colonialism, the Islamic economic system was largely ignored at the governmental level. Today, especially in the last half of the last century, a new wave of awareness, consciousness and enthusiasm has given rise to a number of important steps, including the establishment of financial institutions where Muslims conduct their financial affairs in accordance with Islamic teachings. Contemporary Islamic economy and finance is very successful in achieving its desired position and is rapidly gaining a foothold in the global economy. Islamic Financial Services Industry (IFSI) is offering legitimate alternatives to almost all sectors of the current economic system. Islamic financial industry is a perfect system in terms of its size, comprehensiveness and versatility. This industry includes central and subsidiary Islamic financial institutions that are endeavoring to provide professional services in all financial fields in accordance with Sharīʻah principles.
Keywords: Islamic financial institutions; introduction